Effect of laser preparation on adhesion of a self‐adhesive flowable composite resin to primary teeth. Issue 4 (17th February 2016) - Memarpour, Mahtab; Shafiei, Fereshteh; Razmjoei, Faranak; Kianimanesh, Nasrin
Abstract: The aim of the study was to evaluate the adhesion of a self‐adhering flowable composite resin to primary tooth enamel and dentin after silicon carbide paper (SiC) and laser pretreatment. Adhesive properties were evaluated as shear bond strength (SBS) and scanning electron microscopic (SEM) characteristics. A total 120 primary canine teeth were randomly divided into two groups to study enamel and dentin. Each group was divided into 6 subgroups ( n  = 10) according to type of surface preparation (SiC or Er:YAG laser) of enamel or dentin. Three methods were used to build cylinders of restoration on tooth surface: OptiBond All‐In‐One + Premise Flowable composite, OptiBond All‐In‐One + Vertise Flow and Vertise flow. After restoration, samples were tested for SBS and failure mode. Twenty eight samples were examined by SEM. The results of the study showed SBS of Vertise Flow was lower than others in enamel and dentin samples pretreated with SiC and in dentin samples pretreated with laser ( P  < 0.001). Compared to SiC pretreatment, laser pretreatment led to a significantly higher SBS with Vertise Flow on enamel ( P  < 0.001). Vertise Flow associated with the adhesive led to a higher SBS in enamel and dentin compared to Vertise Flow alone. Adhesive and mixed failure modes were observed more frequently in Vertise Flow groups. SEM images showed that Vertise Flow led to more irregularities on enamel and more open dentinal tubules after laser ablation compared SiC pretreatment. Microsc. Res. Tech. 79:334–341, 2016 . © 2016 Wiley Periodicals, Inc.